E Evaluasi Perspektif Mahasiswa Terhadap Penanganan Banjir di Kota Medan dan Dampaknya terhadap Lingkungan Kampus Universitas Negeri Medan - RADJA MARIHAT BATU BARA; BONARAJA PURBA; JOAN AGUS SIRAIT; ALI ASDON TANJUNG (Jurnal Ekonomi dan Bisnis (EK dan BI), 2023)
In recent years, the city of Medan has experienced frequent flooding, which has affected the campus environment of Medan State University. This study aims to assess students' opinions on flood management in the city of Medan and its impact on the campus environment of Medan State University. Data collection methods were carried out through interviews and observations of Medan State University students. The results showed that students have different opinions about flood management in the city of Medan and its impact on the campus environment of Medan State University. Some students consider that flood management in Medan city is still ineffective and has a negative impact on the campus environment, while others consider that flood management is quite good and has no real impact on the campus environment. Therefore, better and more effective flood management efforts are needed in the city of Medan so that it does not have a negative impact on the campus environment of Medan State University.